ANTESEDEN AUDIT DELAY PADA EMITEN LQ 45 DI BURSA EFEK INDONESIA - Dionysia Kowanda; Rowland Fernando Bismark Pasaribu; Fikriansyah Fikriansyah (Fakultas Bisnis UKDW, 2016)
This study aims to examine and analyze empirically the effect of net profit margin, debt to equityratio, company size, type of industry, reputable company KAP, the audit committee, the age of thecompany, and insider ownership in the issuer's audit delay LQ45 in Indonesia Stock Exchange period2008 -2013. Results of the study are partially, DER, CLASS, COMMITTEE, and Age significant effecton Audit Delay, while NPM, Size, and Insider Ownership no significant effect on the Audit Delay.Based on the coefficient of determination, it turns out all independent variables can only explainAudit Delay variation of 10.4 percent.Keywords: audit delay, net profit margin, debt to equity ratio, size of company, type of industry,reputable company kap, the audit committee, the age of the company, insider ownership